THE EFFECT OF CAGE DENSITY ON SEVERAL HEALTH VARIABLES OF ETAWAH CROSSBREDS IN PEMPATAN VILLAGE KARANGASEM REGENCY BALI - S. H., PITALOKA; DOLOKSARIBU, L.; SARINI, N. P. (Majalah Ilmiah Peternakan, 2024)
Cage density, sanitation frequency, and cage type affect on animal wellbeing and cage environment thus the he- alth of goats. However, its benefits on animal’s health have not been well applied by farmers in Bali. This study was conducted from March until July 2021 to observe the effect of cage density on health variables of PE goats reared by farmers in Pempatan Village. A Compare Means T-test research design with two comparisons of 3 and 2.1 m2/ goat cage density with three replications using 90 goats used in this study. Parameters observed were FAMACHA© score, body weight, ADGW, endo-parasite, level of red and white blood cells of goats. Results showed the cage den- sities had significant differences only for Paramphistomum sp.; goats in cage density 3 m2/goat were not infected by, whereas goats in cage density 2.1 m2/goat got infected by 1.11 ± 0.76 EPG. Ostertagia sp., and Haemoncus contortus sp. infected goats in both densities, but were categorized as mild. The cage density 3 and 2.1 m2/goat had ADGW of 81.74 ± 32.01 g and 48.29 ± 25.51 g, respectively. Goats in this study had standard of healthy goats. In summary, goats in cage density 3 m2/goat tended having better health statuses.